2014
DOI: 10.2741/4261
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy expenditure in diet-induced obese rats

Abstract: Development of obesity in animals is affected by energy intake, dietary composition, and metabolism. Useful models for studying this metabolic problem are Sprague-Dawley rats fed low-fat (LF) or high-fat (HF) diets beginning at 28 days of age. Through experimental design, their dietary intakes of energy, protein, vitamins, and minerals per kg body weight (BW) do not differ in order to eliminate confounding factors in data interpretation. The 24-h energy expenditure of rats is measured using indirect calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 99 publications
(113 reference statements)
1
30
0
1
Order By: Relevance
“…c LPS + AKG group (piglets which were fed the basal diet supplemented with 1 % AKG and challenged with LPS). Normal liver cell cords, mild vacuolation of hepatocytes, limited infiltration of inflammatory leukocytes, and the normal structure of hepatocytes were observed in the LPS + AKG group ◂ (Assaad et al 2014b). At the supplemental dose, dietary AKG can enter the portal circulation and then the liver, as indicated by changes in hepatic concentrations of amino acids (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…c LPS + AKG group (piglets which were fed the basal diet supplemented with 1 % AKG and challenged with LPS). Normal liver cell cords, mild vacuolation of hepatocytes, limited infiltration of inflammatory leukocytes, and the normal structure of hepatocytes were observed in the LPS + AKG group ◂ (Assaad et al 2014b). At the supplemental dose, dietary AKG can enter the portal circulation and then the liver, as indicated by changes in hepatic concentrations of amino acids (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…Its subsequent studies have demonstrated that high-fat diets cause hyperglycemia and insulin resistance (Assaad et al 2014; Pound et al 2014). Studies have also indicated that high consumption of saturated fat acids and cholesterol leads to increased blood cholesterol and LDL (Pound et al 2014) and increased risk of heart diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection for oxygen consumption (VO 2 ), carbon dioxide production (VCO 2 ), respiratory exchange ratio (RER), and energy expenditure (kcal/day) were determined by indirect calorimetry, as previously described (Assaad et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Rats were single-housed in metabolic measurement cages (CLAMS from Oxymax instrument, Columbus Instruments, OH) for the duration of the experiment. Data collection for oxygen consumption (VO 2 ), carbon dioxide production (VCO 2 ), respiratory exchange ratio (RER), and energy expenditure (kcal/day) were determined by indirect calorimetry, as previously described (Assaad et al 2014).…”
Section: In Vivo Assessment Of Rat Metabolic Profilementioning
confidence: 99%